Mimicking nature to control bio-material surface wetting and adhesion - Li,M; Li,C; Blackman,BRK; Eduardo,S (International Materials Reviews, 2021)
Nature has developed unique strategies to refine and optimise structural performance. Using surfaces designed at multiple length scales, from micro to nano levels, combined with complex chemistries, different natural organisms can exhibit similar wetting but different adhesion to liquids under specific environments. These biological surfaces have inspired researchers to develop new approaches to control surface wetting and liquid behaviour via surface adhesion. Here we review natural strategies to control the interaction of liquids with solid surfaces and the efforts to implement these strategies in synthetic materials designed to work in either atmospheric or underwater environment. Particular attention is paid to droplet behaviour on the special-adhesion surfaces in nature and artificial smart surfaces. We highlight recent progress, identify the common threads, and discuss the fundamental differences in a way that can help formulate rational approaches towards surface engineering, and identify current challenges as well as future directions for the field.